RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Protective effect of indomethacin in renal ischemia-reperfusion injury in mice - Sheng-hong Zhu; Li-jia Zhou; Hong Jiang; Rong-jun Chen; Chuan Lin; Shi Feng; Juan Jin; Jiang-hua Chen; Jian-yong Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

A Proteomic Analysis of Placental Trophoblastic Cells in Preeclampsia–Eclampsia - Kaidong Ma; Hong Jin; Rong Hu; Yu Xiong; Shufeng Zhou; Peng Ting; Yan Cheng; Yan Yang; Pengyuan Yang; Xiaotian Li (Cell Biochemistry and Biophysics, 2014)

Distribution and geochemical characteristics of fluids in Ordovician marine carbonate reservoirs of the Tahe Oilfield - Mei Li; Zhanghua Lou; Rong Zhu; Aimin Jin; Ying Ye (Journal of Earth Science, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Effects of land cover on soil organic carbon stock in a karst landscape with discontinuous soil distribution - Xiang-bi Chen; Hua Zheng; Wei Zhang; Xun-yang He; Lei Li; Jin-shui Wu; Dao-you Huang; Yi-rong Su (Journal of Mountain Science, 2014)

Overexpression of S100P promotes colorectal cancer metastasis and decreases chemosensitivity to 5-FU in vitro - Lei Dong; Fule Wang; Xiaona Yin; Ling Chen; Gang Li; Feiyan Lin; Wuhua Ni; Jianbo Wu; Rong Jin; Lei Jiang (Molecular and Cellular Biochemistry, 2014)

Cloning and expression analysis of a novel high-mobility group box 2 homologue from Lampetra japonica - Pang Yue; Xiao Rong; Xue Zhuang; Huang Jin Sha; Jin Min Li; Liu Xin; Qing Wei Li (Fish Physiology and Biochemistry, 2014)

C and N stable isotope analysis of human and animal bones at the Beiqian site - Fen Wang; YanBo Song; BaoShuo Li; Rong Fan; GuiYun Jin; ShiLing Yuan (Science China Earth Sciences, 2014)

An improved embryo-rescue protocol for hybrid progeny from seedless Vitis vinifera grapes × wild Chinese Vitis species - Gui Rong Li; Wei Ji; Gang Wang; Jian Xia Zhang; Yue Jin Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Diversity of bacterioplankton in coastal seawaters of Fildes Peninsula, King George Island, Antarctica - Yin-Xin Zeng; Yong Yu; Zong-Yun Qiao; Hai-Yan Jin; Hui-Rong Li (Archives of Microbiology, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)